School-Time Movement Behaviors and Fundamental Movement Skills in Preschoolers: An Isotemporal Reallocation Analysis. Issue 4 (August 2021) - Martins, Clarice Maria de Lucena; Clark, Cain Craig Truman; Tassitano, Rafael Miranda; Filho, Anastácio Neco de Souza; Gaya, Anelise Reis; Duncan, Michael Joseph
Little is known of how reallocations of time spent in different movement behaviors during preschool might relate to preschoolers' fundamental movement skills (FMS), a key predictor of later physical activity (PA). Thus, the aim of this study was to examine (a) whether preschoolers' school-time movement was associated with their FMS and (b) the effects on FMS of reallocating time between PA and sedentary behavior (SB). This was a cross-sectional study, using intervention data with Brazilian low-income preschoolers. We observed Brazilian preschoolers of both sexes ( M age  = 4.5, SD  = 0.8 years-old; 101boys) over 10 hours of school-time and objectively assessed their PA and SB with Actigraph wGT3X and their FMS with the Test of Gross Motor Development – Second Edition. We explored the associations between school-time movement behaviors and FMS and between reallocated school-time movement behaviors and FES using compositional analysis in R (version 1.40-1), robCompositions (version 0.92-7), and lmtest (version 0.9-35) packages. This isotemporal reallocation showed that, for manipulative skills, reallocating time (5, 10, and 15 minutes, respectively) from light PA to SB was associated with increasing skill (0.14, 0.28, and 0.42 FMS units), raising questions as to whether fine motor activity occurred during SB. Thus, school-time movement significantly predicted FMS, with a modest increase in SB, at the expense of light PA eliciting improved manipulative skills.